Direct-to-implant Prepectoral Breast Reconstruction in Women Older Than 65 Years: Analysis of Safety and Patient-reported Outcome - Adi Maisel Lotan, MD; Yotam Teldan, MD; Ronen Toledano, MD; Shahar Talisman, MD; Shalom Strano, MD; Hadar Goldvaser, MD; Tal Zobok, MD; Yoav Gronovich, MD, MBA (Plastic and Reconstructive Surgery, Global Open)
Background:. Immediate breast reconstruction following mastectomy has many proven advantages. Although more than half of the patients with breast cancer in the United States are older than 65 years of age, breast reconstruction rates in this age group are low. The goal of this study was to evaluate safety and patient satisfaction of direct-to-implant (DTI) prepectoral breast reconstruction in women older than 65 years of age. Methods:. This was a retrospective, single-center study of 56 women (56 breasts) undergoing DTI prepectoral breast reconstruction. Twenty-eight patients were older than the age of 65 years and 28 were younger. Groups were matched for surgical procedure, smoking status, body mass index, and history of radiation therapy. Outcomes were compared between groups, and possible correlations were studied. Results:. Twelve patients older than 65 years of age had hypertension (P = 0.007). Perioperative pain management, major complications, total number of surgical complications, reconstruction failure, and duration of hospitalization were similar in both groups. More advanced age was correlated with higher psychosocial well-being, sexual well-being and satisfaction with breasts on the BREAST-Q scale. Median follow-up was 11.5 months (older) and 23 months (younger). Conclusions:. Prepectoral DTI breast reconstruction in women older than 65 years of age is safe, reproducible, has high patient satisfaction, and may be performed in this patient cohort.